The influence of work experience and communication on secretary performance in five star hotels in Bali - Kasiani Kasiani; I Made Sarjana; Lily Marheni; Upayana Wiguna Eka Saputra; Anak Agung Ayu Mirah Kencanawati (Universitas Negeri Yogyakarta, 2023)
The purpose of this study was to examine the impact of work experience and communication on the performance of secretaries at Bali's Five-Star Hotels. This study was quantitative in nature. In this study, the population consisted of 98 secretaries from 50 five-star hotels in Bali that had been registered since 2021. This study's sample consisted of 98 Executive Secretaries and Departmental Secretaries selected using the side saturation or “Sampling Jenuh” technique. The data used were primary data derived from respondents' responses, which were then analyzed using multiple linear regression analysis techniques. The strategy for collecting data consisted of a Google Form questionnaire. In this study, it was found that 1) work experience has a positive and substantial influence on secretary performance, 2) communication has a positive and significant influence on secretary performance, and 3) both work experience and communication have a positive and significant influence on secretary performance. As for the guidance that may be given to Five Star Hotels in Bali, particularly the secretarial division, it is suggested that the secretary's excellent performance must be supported by a high level of commitment to performing responsibilities in line with the job description.